Addressing Trauma in Early Childhood—Shaping Education, Policy, and Actionable Strategies in Ireland: A Qualitative Study - Catherine Sheehan; Judith Butler; Cian O’Neill (Education Sciences)
The breadth and volume of research exploring the complexities of childhood trauma in Early Childhood Education and Care (ECEC) environments has grown significantly in recent years, yet, little is known about this trajectory in an Irish context. Consequently, the purpose of the current study was twofold: (i) consult with influential figures in the wider ECEC domain to access expert knowledge on the provision of trauma awareness education in Ireland and to (ii) gain invaluable insights into the trauma awareness knowledge, training, and experiences of ECEC professionals working in Irish ECEC settings. Utilising a qualitative methodological approach, eight semi-structured interviews with ECEC sector representatives (i.e., IV Group) and six focus groups with managers (n = 8), room leaders (n = 8), and practitioners (n = 8) (i.e., FG Group) were conducted as explorative processes to investigate the presence of trauma awareness in ECEC, if any, and the factors supporting/hindering this discourse from the perspectives of diverse stakeholders and professionals in Ireland. Results revealed that the provision of trauma awareness is challenged by the dearth of relevant educational opportunities during both Initial Practitioner Education (IPE) and Continuous Professional Development (CPD) pathways, with an absence of neuro-informed practice among the FG Group. Contrastingly, while sector representatives in the IV Group demonstrated an awareness of childhood trauma, these participants identified the need for (i) government investment, (ii) training reform, and (iii) professional practice considerations. Based on the cumulative findings, this research recommends that policymakers in Ireland prioritise the provision of funded and/or incentivised professional development opportunities for the ECEC profession to enhance the knowledge and skills associated with trauma-informed practice.